When to stop computing and start investing - Sean R. Aguilar; Olga Kosheleva (Asian Journal of Economics and Banking (AJEB), 2021)
Purpose - The purpose of the study is to analyze when - while predicting the future price of a financial instrument - we should stop computations and start using this information for the actual investment. Design/methodology/approach - We derive the explicit formulas explaining how the resulting gain depends on the duration of computations. Findings - We provide an algorithm that enables us to decide the computation time that leads to the largest possible gain. Originality/value - To the best of our knowledge, this is the first solution to the problem. Following our recommendations will allow investors to select the computation time for which the resulting gain is the largest possible.
Keywords: 330; Investment; Optimal investment portfolio; Computation time